Effects of Parent-Teacher Training on Academic Performance and Parental Anxiety in School-Aged Children With Attention-Deficit/Hyperactivity Disorder: A Cluster Randomized Controlled Trial in Shanghai, China - Shen, Li; Wang, Chunxia; Tian, Yuan; Chen, Jinjin; Wang, Yu; Yu, Guangjun (Frontiers in Psychology, 2021)
Background: Attention Deficit/Hyperactivity Disorder (ADHD) is the most common chronic neurodevelopmental disorder of childhood, placing a heavy burden on families and society. The treatment of school-aged children with ADHD emphasizes multimodal interventions, but most current research focuses solely on parent training and family functioning, neglecting the role of schools for children with ADHD. The aim of this study was to examine the effect of parent-teacher training on academic performance and parental anxiety. Methods: In an open-label cluster randomized controlled trial from January 2018 to January 2019, 14 primary schools in Shanghai were randomly assigned into intervention group and control group and ADHD screening was conducted for students from grades one to five. The control group was treated with conventional medication and the intervention group was treated with medication combined with parent-teacher training. The training includes ADHD behavioral interventions for parents, as well as classroom management skills for teachers. The cluster randomized controlled trial was conducted to investigate the effect and acceptability of this training at 4 months and 10 months. It was registered as a clinical trial at clinical trials.gov, registration number: ChiCTR1800014945. Results: This cluster randomized controlled trial screened 9295 students, 99 children in the control group and 105 children in the intervention group were included in the analysis. The intervention group demonstrated significant improvement in academic performance and decreases in parent stress compared to that in the control group(P<0.05). This training improved the parents’ perception of ADHD knowledge, treatment options and drug side effects awareness(P<0.05). Conclusion: Our study aims to underscore the suitability of such programs in the local nuances of the Chinese context, show application feasibility to pediatricians and psychiatrists, and provide supporting evidence for their utilization within the country’s health and educational systems.